Macrophage migration inhibitory factor drives neutrophil accumulation by facilitating IL-1β production in a murine model of acute gout. Issue 6 (11th February 2016) - Galvão, Izabela; Dias, Ana Carolina Fialho; Tavares, Livia Duarte; Rodrigues, Irla Paula Stopa; Queiroz-Junior, Celso Martins; Costa, Vivian Vasconcelos; Reis, Alesandra Corte; Ribeiro Oliveira, Rene Donizeti; Louzada-Junior, Paulo; Souza, Daniele Glória; Leng, Lin; Bucala, Richard; et al.
Abstract : MIF plays an important role in the initial process of gout via the control of IL-1β. Abstract: This study evaluated the role of macrophage migration inhibitory factor in inflammation caused by monosodium urate crystals. The concentration of macrophage migration inhibitory factor was increased in synovial fluid of patients with acute gout, and there was a positive correlation between intra-articular macrophage migration inhibitory factor and IL-1β concentrations. In mice, the injection of monosodium urate crystals into the knee joint increased the levels of macrophage migration inhibitory factor in macrophages and in inflamed tissue. The injection of recombinant macrophage migration inhibitory factor into the joint of mice reproduced the inflammatory response observed in acute gout, including histologic changes, the recruitment of neutrophils, and increased levels of IL-1β and CXCL1. Importantly, the accumulation of neutrophils and the amount IL-1β in the joints were reduced in macrophage migration inhibitory factor-deficient mice when injected with monosodium urate crystals. We observed a similar effect when we blocked macrophage migration inhibitory factor with (S, R)-3-(4-hydroxyphenyl)-4, 5-dihydro-5-isoxazole acetic acid or anti-macrophage migration inhibitory factor. In addition, the blockade of IL-1R and CXCR2 reduced recombinant macrophage migration inhibitory factor-induced neutrophil recruitment. Mechanistically, recombinant macrophage migration inhibitory factor is important for the synthesis of il1β mRNA in vivo and in isolated macrophages. Altogether, macrophage migration inhibitory factor promotes neutrophil accumulation and is important for IL-1β production, which are 2 crucial events contributing to the pathogenesis of acute gout.